Information Technology in the Implementation of Land Registration Activities: The Implementation Side - Riswandar, Muhammad Rafli; Abbas, Ilham (Golden Ratio of Law and Social Policy Review, 2023)
This study aims to determine how the implementation of land registration activities through information technology activities at the Regional Office of the National Land Agency of South Sulawesi Province in the Division of Determination and Registration of Rights and what factors affect land registration activities through the application of information technology at the Regional Office of the National Land Agency of South Sulawesi Province in the Division of Determination and Registration of Rights. The results of this study indicate that the implementation of land registration activities through the application of Information Technology in the Regional Office of the National Land Agency of South Sulawesi Province was implemented on Law of Information and Electronic Transactions. In addition, related to the implementation of technology utilization, of course, there are problems that are present, one of which is external factors in land registration, community factors are very influential on the smooth process of land registration activities. Without community support, community activities will not run effectively. And internal factors sociologically, every law enforcer has a position and role. The position is a container in which certain rights and obligations are contained. In order for this to work as desired, the author suggests that there needs to be more attention to communication aspects and aspects of service quality at the Regional Office of the National Land Agency of South Sulawesi Province in the Division of Determination and Registration of Rights. This is because there are still employees who do not understand the national land management information system policy well. And it is also necessary to improve the quality of service by paying attention to supporting factors in making services easier and faster. And the need for additional human resources or recruitment of new employees who are able to apply Information Technology, the need to improve the quality of a better internet network and improve/update existing hardware and application software and improve KKP applications managed by the central BPN, and the need for counseling/understanding of land registration activities to the community.